Molecular mechanisms leading to ceftolozane/tazobactam resistance in clinical isolates of Pseudomonas aeruginosa from five Latin American countries - Mojica, María F.; De La Cadena, Elsa; Ríos, Rafael; García-Betancur, Juan Carlos; Díaz, Lorena; Reyes, Jinnethe; Hernández-Gómez, Cristhian; Radice, Marcela; Gales, Ana C.; Castañeda Méndez, Paulo; Munita, José M.; Pallares, Christian José; et al. (Frontiers in Microbiology, 2022)
Objectives: we identified the molecular mechanisms responsible for the in vitro non-susceptibility to ceftolozane/tazobactam (TOL) in a group of 158 clinical isolates of P. aeruginosa from five Latin American countries collected before the introduction of TOL into the clinical practice. Methods: clinical isolates of P. aeruginosa (n=504) were collected between Jan 2016 and Oct 2017 from 20 hospitals located in Argentina, Brazil, Chile, Colombia, and Mexico. Minimum inhibitory concentrations (MICs) to TOL were determined by standard broth microdilution and interpreted according to CLSI breakpoints. Initially, production of carbapenemases in TOL non-susceptible isolates was assessed by Rapidec® followed by qPCR to detect blaKPC, blaNDM-1, blaVIM and blaIMP. Illumina® WGS was performed for isolates in which non-susceptibility to TOL was not mediated by carbapenemases. Results: a total of 158 (31.3%) isolates were non-susceptible to TOL. In 74 (46.8%) of these isolates, non-susceptibility to TOL was explained by the production of at least one carbapenemase. WGS revealed that some isolates carried ESBLs, mutated blaPDC and ampD, associated with decreased susceptibility to TOL. Conclusions: substitutions found in PDC and carbapenemase production were the most common presumed mechanism of resistance to TOL detected in this study. This study shows that epidemiological surveillance is warranted to monitor the emergence of novel mechanisms of resistance to TOL that might compromise its clinical utility.